Photonic bandgaps in selectively filled photonic crystal fibers - Jaworska, Olga H.; Ertman, Sławomir (Photonics Letters of Poland, 2017)
Simulations of selectively filled photonic crystal fibers using finite elements method were performed. Different patterns of filling were modeled and compared to an empty and fully filled fiber. Dependence of effective refractive indices of guided modes, phase birefringence and confinement losses on guided wavelength was investigated. A comparison of width of photonic bandgaps in different structures was made. Full Text: PDF References Ph. St. J. Russell, "Photonic-Crystal Fibers", J. Lightwave Technol. 24, 4729 (2006) CrossRef Y. Han, S. Tan, M. K. K. Oo, D. Pristinski, S. Sukhishvili, and H. Du, "Towards Full-Length Accumulative Surface-Enhanced Raman Scattering-Active Photonic Crystal Fibers", Adv. Mat. 22, 2647 (2010) CrossRef S. Ertman, A. H. Rodríguez, M. M. Tefelska, M. S. Chychłowski, D. Pysz, R. Buczyński, E. Nowinowski-Kruszelnicki, R. Dąbrowski, and T. R. Woliński, "Index Guiding Photonic Liquid Crystal Fibers for Practical Applications", J. Lightwave Technol. 30, 1208 (2012) CrossRef K. Mileńko, S. Ertman, T. R. Woliński, "Numerical Analysis of the Phase Birefringence of the Photonic Crystal Fibers Selectively Filled with Liquid Crystal", Mol. Cryst. Liq. Cryst. 596, 4 (2014) CrossRef Y. Wang, C. Liao, X. Zhong, Z. Li, Y. Liu, J. Zhou, and K. Yang, "Selective-fluid-filled photonic crystal fibers and applications", Proc. SPIE 8914, 89140J-1 (2013) CrossRef F. Wang, W. Yuan, O. Hansen, and O. Bang, "Selective filling of photonic crystal fibers using focused ion beam milled microchannels", Opt. Express 19, 17585 (2011) CrossRef T. Martynkien, G. Statkiewicz-Barabach, J. Olszewski et al., "Highly birefringent microstructured fibers with enhanced sensitivity to hydrostatic pressure", Opt. Express 18, 15113 (2010) CrossRef B. T. Kuhlmey, R.C. McPhedran, C. M. de Sterke, "Modal cutoff in microstructured optical fibers", Opt. Lett. 27, 1684 (2002) CrossRef